2017
DOI: 10.21037/acs.2017.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical and transcatheter aortic valve replacement in the octogenarians—surgery still the gold standard?

Abstract: Background: Contemporary options for aortic valve replacement (AVR) include transcatheter and surgical approaches (TAVR and SAVR). As evidence accrues for TAVR in high and intermediate risk patients, some clinicians advocate that all patients aged over 80 years should only receive TAVR. Our aim was to investigate the utility of SAVR and minimally invasive AVR (mAVR) among octogenarians in the current era of TAVR. Results: Compared to SAVR patients, TAVR patients were relatively older (86.2 versus 84.2 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
3
18
1
Order By: Relevance
“…However, the risk scores may be misleading in the ≥80-year-old patients, as peri-operative complications exist beyond the scores, owing to frailty and very old age per se [71][72][73]. Nonetheless, the current data demonstrate that TAVR is beneficial in octogenarians [70][71][72][73][74][75][76][77] as well as in >90-year-old patients [75,76]. Furthermore, a recent study [76] conducted with asymptomatic patients with very severe AS aged between 20 and 80 years has proven that the incidence of operative mortality or death from a cardiovascular cause was significantly lower in those treated with early surgical aortic valve replacement compared to those who received conservative care.…”
Section: Valve Heart Diseasesmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the risk scores may be misleading in the ≥80-year-old patients, as peri-operative complications exist beyond the scores, owing to frailty and very old age per se [71][72][73]. Nonetheless, the current data demonstrate that TAVR is beneficial in octogenarians [70][71][72][73][74][75][76][77] as well as in >90-year-old patients [75,76]. Furthermore, a recent study [76] conducted with asymptomatic patients with very severe AS aged between 20 and 80 years has proven that the incidence of operative mortality or death from a cardiovascular cause was significantly lower in those treated with early surgical aortic valve replacement compared to those who received conservative care.…”
Section: Valve Heart Diseasesmentioning
confidence: 77%
“…MVR has a high short-term mortality of 25%-30%, and the limited life-expectancy of old patients, the lower technical complexity of SMVR with shorter cardio-pulmonary bypass times, and a decreased risk of failure with a requirement for reintervention may explain the lower-than-expected rate of MVR [80]. Nonetheless, in octogenarian patients, 15% operative mortality has been reported for SMVR [76]. At present, according to the administrative American databases, MVR was performed in less than 50% of the elderly patient cases [81][82][83][84][85][86][87].…”
Section: Valve Heart Diseasesmentioning
confidence: 99%
“…This 13-year study revealed that in-hospital mortality was similar among groups of surgical AVR and TAVR. Importantly, mid-and long-term survival analysis (52 months) showed that surgical intervention had significantly better long-term survival compared to the TAVR group at 12, 24, 36, and 48 months survival was 86, 82, 78, and 73%, respectively, for surgical AVR versus 83, 75, 64, and 52% survival for TAVR (p = 0.024) [33]. Therefore, authors concluded that the surgical approach via full sternotomy is safe and should be still offered as a treatment option even in the elderly population [33].…”
Section: Safety Of Surgical Avr In the Modern Eramentioning
confidence: 96%
“…The study demonstrated that surgical AVR, MIA-VR, and TAVR had no difference in early mortality [32]. In another observational, single-center study of 1,028 octogenarian patients from 2002 to 2015, the outcomes after TAVR, surgical AVR, and MIAVR were compared [33]. This 13-year study revealed that in-hospital mortality was similar among groups of surgical AVR and TAVR.…”
Section: Safety Of Surgical Avr In the Modern Eramentioning
confidence: 99%
See 1 more Smart Citation